Gender and holiness : men, women, and saints in late medieval Europe - Riches, Samantha; Salih, Sarah, 1967- (Routledge studies in medieval religion and culture ;, 2002)
This volume examines gender-specific religious practices and contends that the pursuit of holiness can destabilize binary gender itself. Though saints may be classified as masculine or feminine, holiness may also cut across gender divisions and demand a break from normally gendered behaviour.